GPS deformation monitoring and analysis for local cors network: Iskandarnet - Lim, M. C. (Faculty of Geoinformation and Real Estate, Universiti Teknologi Malaysia, 2010)
Monitoring of deformation in urban areas is of great importance, providing useful information to assess seismic hazards and risks. Thus, this study concerns the feasibility using Continuously Operating Reference Stations (CORS) in Iskandar metro-area (termed ISKANDARnet) for deformation monitoring and analysis. A strategy is developed that using three GPS CORS from ISKANDARnet as the object monitoring stations along with nearby International GNSS Services (IGS) stations (e.g. NTUS, XMIS, COCO and PIMO) as the reference monitoring stations. GPS data is streamed and processed by the high precision scientific GPS data processing software module, called Bernese Processing Engine (BPE) in persistent processing strategic. A software package in Matrix Laboratory (MATLAB) language has been developed to conduct a continuous two-epoch analysis by implementing the Iteratively Weighted Similarity Transformation (IWST) method and Similarity Transformation (S-Transformation) to analyse the GPS results in the deformation perspective. With the performance of IWST and S-Transformation, the unstable point able to be identified within the monitoring network as well as compute the deformation displacement vectors. The fluctuation of deformation displacement is visualised on-screen proportional to the associated time series results. Several preliminary works and analysis are stated in this paper. This study will bring the invaluable contribution to the current studies of deformation analysis in Malaysia.